Tensile Strength of Adhesively Bonded Steel to Hybrid Sisal-Glass Reinforced HDPE Composite Joint for Automobile Side Body Panel Application - Samuel Tesfaye Molla; Assefa Asmare Tsegaw; Teshome Mulatie Bogale; Addisu Negash Ali; Asmamaw Tegegne Abebe (Journal of Fibers and Polymer Composites, 2026)
The increasing demand for lightweight, high-performance, and environmentally sustainable materials in the automotive industry has accelerated the adoption of adhesive bonding as an alternative to conventional joining techniques such as welding and mechanical fastening. Reliable prediction of stress distribution and debonding behavior in adhesively bonded composite–metal joints is therefore essential to ensure structural integrity under service loading. This study presents a comprehensive computational and experimental investigation of the tensile stress behavior of adhesively bonded single-side strap joints (ABSSSJ) formed between steel and hybrid sisal–glass reinforced high-density polyethylene (HDPE) composites for automobile side body panel applications. The hybrid composite adherend was modeled as an orthotropic laminate with a ([0°/+45°/90°/–45°/0°]) stacking sequence, while the adhesive layer was characterized using different epoxy systems (Araldite 2020, Araldite 2015, and AV138) with thicknesses ranging from 0.12 to 1.0 mm and elastic moduli between 1.85 and 6 GPa. An analytical variational method was employed to evaluate shear and peel stress distributions, and the results were verified using a cohesive zone model (CZM)-based finite element approach to simulate crack initiation and progressive debonding. Experimental tensile and shear tests were conducted to validate the numerical predictions. The results indicate that an adhesive thickness of approximately 0.75 mm provides an optimal balance between load transfer efficiency and stress reduction at the overlap edges. The numerical and analytical predictions exhibited strong agreement with experimental measurements, with a maximum deviation below 6%. The validated results demonstrate that hybrid sisal–glass reinforced HDPE composites, when combined with appropriate adhesive and joint design, offer a promising, lightweight, and sustainable solution for automotive side body panel structures.